2003
DOI: 10.4314/bcse.v17i1.61731
|View full text |Cite
|
Sign up to set email alerts
|

<b>Synthesis and fungicidal activity of acetyl substituted benzyl disulfides</b>

Abstract: The synthesis and fungicidal activity of acetyl substituted benzyl disulfides 1(a ---g) are reported. The compounds were characterized by elemental analysis, nuclear magnetic resonance ( 1 H NMR and 13 C NMR) and mass spectrometric techniques. The results of the biological screening showed that the synthesized compound possess very high fungicidal activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Ayodele et al carried out the synthesis of unsymmetrical disuldes from thiol, thiourea and thioacetic acid. 10 The method involved the reaction of thiol and thiourea, the latter acts as the S-transfer agent, to form an intermediate S-benzylthioisothiouronium chloride 2 that nally reacts with thioacetic acid (Scheme 4).…”
Section: Methods Of Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Ayodele et al carried out the synthesis of unsymmetrical disuldes from thiol, thiourea and thioacetic acid. 10 The method involved the reaction of thiol and thiourea, the latter acts as the S-transfer agent, to form an intermediate S-benzylthioisothiouronium chloride 2 that nally reacts with thioacetic acid (Scheme 4).…”
Section: Methods Of Synthesismentioning
confidence: 99%
“…9 Unsymmetrical disuldes have fungicidal properties. 10 In a recent study, it is revealed that oxidized species of disuldes, such as thiosulnate or thiosulfonate may operate as a rst line of the body's defense against cyanide intoxication. 11 Moreover, disuldes nd vast applications in agro-chemicals, as shown by large varieties of new sulfur-based crop protection chemicals around the world.…”
Section: Introductionmentioning
confidence: 99%
“…10 Ayodele et al reported the fungicidal activity of benzyl disulfides. 11 In industry, the disulfides have wide applications such as vulcanizing agents for rubbers 12 and in the design of lithium-ion batteries. 13,14 These compounds have a key role in synthetic organic chemistry as they are used for the synthesis of heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of organic disulphide compounds by the oxidation of thiol derivatives has become a common practice, and quite a few methodologies have been developed in the preparation of these compounds [8] [9]. There has been an increasing demand for novel, ecofriendly and efficient methodologies for the synthesis of organic disulphide compounds owing to their importance in a wide range of pharmaceutical and agro-chemical applications [10] [11].…”
Section: Introductionmentioning
confidence: 99%